Analisis Gerak Semu Matahari terhadap Kegiatan Aktivitas Bumi - Ester Y.F Simamora; Muhammad Arif; Elsa Kardiana; Hotdame Martina Sitanggang; Putri Roito Lumbantobing; Vinny Natasya Hura; Yunilawati Patrisa Panjaitan (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to analyze the effect of the apparent movement of the sun on community activity patterns, The method used is qualitative descriptive research with a literature study approach and secondary data analysis from various scientific studies. The results of the study indicate that the apparent movement of the sun significantly affects the division of community activity time, both daily, economic and social activities. Adjusting activities to the position of the sun also has an impact on energy efficiency, environmental comfort and community productivity. This finding is important because understanding the apparent movement of the sun in planning daily activities and managing community time. This study contributes to the development of science int the field of social science education, especially in understanding the relationship astronomic.